(3GdchGcH GdOQjI aj JQGLe GdSGOI GdUhajIs - (3eMeO YHO GdQDha Hf JGL GdYGQajf GHf Ydj Hf Rjf GdYGHOjf GdMOGOj Ke GdefGhj GdbGgQj, Rjf GdOjf ,J (B1031 (3g` s ((3eMeO (B((3cPG(B)q s)
(3ChdgG (B:s
(3GdMeO ddg GdPi SbG ChdjGAg hGYGXe YHGOg ef cCS hOGOg eG CPgdge Yf GdSgGO hGdcQi hTZdge YeG ShGg s
(3BNQgG (B:s
(3hgPG BNQ eG YdbfGg ef GdZQV GdeWdhH HMSH eG JjSQ hMVQ hbO ChOYfGg ef aQGFO GdahGFO eG jTfa GdCSeGYq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf JedcGJs
(3ai Chdg GdfSNI agQSJ HCSeGA GdeJQLe dge hYOOge (B775 (3ai EMOi YTQ hQbI ecJhHI ai LOGhd LejdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B75s
Keywords: (3GdJGQjNs